2017
DOI: 10.1016/j.humimm.2017.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of CX3CR1 on tonsillar CD8-positive cells in patients with IgA nephropathy

Abstract: Although tonsillectomy are used as therapeutic options to prevent chronic renal failure in IgA nephropathy (IgAN) patients, the relationship between IgAN and tonsils is not fully proved by basic research. Recently, circulating CX3CR1-positive cells were reportedly involved in promoting hematuria in patients with IgAN. In this study, we focused on the expression of CX3CR1 in tonsillar mononuclear cells in IgAN patients. Immunohistological analysis revealed greater distribution of CX3CR1-positive cells in the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…The chemotactic response of tonsillar mononuclear cells to fractalkine was significantly higher in patients with IgAN. The expression of CX3CR1 in the peripheral blood CD8 + cells in patients with IgAN was significantly higher and decreased after tonsillectomy, along with the disappearance of hematuria (24). Taken together, the aforementioned studies suggest that CD8 + T cells might be one of the exacerbating factors in patients with IgAN.…”
Section: Cd8 + Cellsmentioning
confidence: 82%
See 1 more Smart Citation
“…The chemotactic response of tonsillar mononuclear cells to fractalkine was significantly higher in patients with IgAN. The expression of CX3CR1 in the peripheral blood CD8 + cells in patients with IgAN was significantly higher and decreased after tonsillectomy, along with the disappearance of hematuria (24). Taken together, the aforementioned studies suggest that CD8 + T cells might be one of the exacerbating factors in patients with IgAN.…”
Section: Cd8 + Cellsmentioning
confidence: 82%
“…However, additional reports also revealed that the strong polarization of Th1 in IgAN, and the advantage of Th1 is associated with the development of renal injury in IgAN (20)(21)(22)(23). In a recent study, the upregulation of CX3CR1 + CD8 + T cells in the tonsils was found in patients with IgAN (24). Taken together, these findings revealed that T lymphocytes play an important role in the development of IgAN.…”
Section: Introductionmentioning
confidence: 86%
“…Notably, Otaka et al demonstrated the upregulation of CX3CR1 on tonsillar CD8+ T cells in patients with IgAN and postulated that a hyper-immune response to microbial DNA enhanced the expression of CX3CR1 on CD8+ T cells in the interfollicular area of palatine tonsils, followed by migration of the cells to renal lesions via the blood circulation, eventually resulting in the development of hematuria [8]. Given that epipharyngeal CD8+ T cells, as a part of NALT, behave in similar fashion to tonsillar interfollicular CD8+ T cells, we postulate that the upregulation of fractalkine/ CX3CR1 interactions related to epipharyngitis may play a crucial role in glomerular vasculitis, resulting in worsening hematuria.…”
Section: Role Of Fractalkine/cx3cr1 Interaction In Iganmentioning
confidence: 99%
“…Immunoglobulin A (IgA) deposition in the glomerular mesangium is the histological hallmark of IgA nephropathy (IgAN) and has led to extensive research on mucosaassociated lymphoid tissue (MALT) since the initial recognition of this disease approximately 50 years ago. MALT governs mucosal immunity and, in particular, the palatine tonsils (organized MALT) [1][2][3][4][5][6][7][8][9][10] and the gut-associated lymphatic tissue [11][12][13][14][15][16][17][18][19] have drawn significant interest.…”
Section: Introductionmentioning
confidence: 99%
“…CX3CL1 is mainly produced by glomerular endothelial cells and the tubular epithelium and can be detected in many other cells, such as podocytes, mesangial cells, renal tumor cells and stromal cells [ 14 - 16 ]. CX3CR1 is a G-protein coupled receptor that is expressed on CD8 + T lymphocytes [ 17 ], mast cells [ 18 ], Natural Killer (NK) cells [ 19 ], Dendritic Cells (DCs) [ 20 ], platelets [ 21 ], renal cancer cells [ 22 ], vascular smooth cells [ 23 ], tubular cells [ 24 ] mesenchymal cells [ 25 ], and monocytes/macrophages [ 26 , 27 ]. After CX3CL1 conjugates with CX3CR1, the CX3CL1/CX3CR1 axis can initiate a cascade via several signaling pathways in the kidney, including ROS/MAPKS, Raf/MEK1/2-ERK1/2-Akt/PI3K, and nuclear factor of kappa light polypeptide gene enhancer in B cells 1 (NF-kB).…”
Section: Introductionmentioning
confidence: 99%